Equivalent transformation and weighted $H_∞$-optimization of linear descriptor systems - Mazko, A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.925.51; 681.5.03We study the problem of generalized $H_∞$-control for a class of linear descriptor systems with nonzero initial vector. We use a generalized performance measure characterizing the weighted level of damping of external and initial disturbances. A nondegenerate transformation of the system is proposed, which allows us to apply well-known methods for the evaluation and attainment of the desired performance criteria for conventional lower-order systems. A numerical example of a controlled hydraulic system with three tanks is presented.